Assessment of micronutrient intake on the prevalence of anemia among pregnant women in a District of Northern India - Dr. J.P. Srivastava, Dr.Sandhya Mishra, Dr.Amit Nandan Mishra, Dr. Pratibha (International Journal of Scientific Research and Management (IJSRM), 2014)
Objective: This study was undertaken to assess the role of micronutrient intake on prevalence of anemia amongst pregnant women in Lucknow Utter Pradesh India Study design: cross-sectional study. Study area: Urban and rural areas of Lucknow. Study subjects: A total of 420 pregnant women of reproductive age group. Results: The overall prevalence of anemia was 73.1% among the pregnant women. Of these, the moderate anemia was found in 47.6% women, mild anemia was 43.6% and severe anemia was 8.8%.The prevalence of anemia was lower in married women as compared to divorced/widow women (RR=0.91, 95%CI=0.59- 1.42, p=0.73). The multivariate logistic regression analysis indicated that the women who were in 4-6 months (OR=4.51, 95%CI=1.95-10.43, p